Effects of scapular-focused movement-based exercises on sports performance of athletes with scapular dyskinesis: A systematic review - Mònica Solana–Tramunt; Hossein Fakoor Rashid; Narges Norouzi; Yaser Dehghan; Hossein Khazanin; Bahareh Sadegh; Mohammad Alimoradi; Hassan Daneshmandi; Mohammad Alghosi (PLoS ONE, 2026)
Background Scapular dyskinesis is a common dysfunction among athletes, particularly in overhead sports, leading to pain, reduced range of motion (ROM), and impaired performance. Movement-based exercises are increasingly used to address these issues, but their overall impact on sports performance remains unclear. Objective This systematic review aims to evaluate the effects of movement-based exercises on sports performance in athletes with scapular dyskinesis. Method A comprehensive search was conducted in Web of Science, Scopus, and PubMed up to July 30, 2025, following PRISMA guidelines. Data were extracted and assessed for risk of bias using RoB-2 and ROBINS-I tools. A narrative synthesis was performed due to study heterogeneity. Results Fourteen studies (8 RCTs and 6 non-RCTs) involving 412 participants with a mean age of 23.8 years assessed movement-based interventions lasting from a single session to 24 weeks, primarily focusing on scapular stabilization, kinetic chain control, and proprioception over 6–8 weeks with around three sessions per week. Moderate-certainty evidence suggests that exercise likely improves shoulder function, disability, and glenohumeral range of motion over 6–12 weeks. However, the evidence for pain reduction and improvement in rotator cuff/scapular strength is of low certainty, showing mixed effects depending on the specific program. Evidence for improvement in scapular kinematics is also of low certainty. Sport-specific performance outcomes, such as throwing velocity, remain highly uncertain due to small sample sizes and conflicting results from RCTs. Conclusion Movement-based exercises may be considered by athletes with scapular dyskinesis to potentially improve shoulder function and glenohumeral range of motion; however, the certainty of evidence for effects on pain relief, strength, and sports performance is very low. Therefore, strong recommendations cannot be made at this stage. More tailored programs and well-structured RCTs are needed to clarify these effects.